Attenuating Renal Interstitial Fibrosis by Shenqi Pill via Reducing Inflammation Response Regulated by NF-κB Pathway In Vitro and In Vivo (Iranian Journal of Kidney Diseases, 2024)
Introduction. One of the most significant clinical features of chronic kidney disease is renal interstitial fibrosis (RIF). This study aimed to investigate the role and mechanism of Shenqi Pill (SQP) on RIF.Methods. RIF model was established by conducting unilateral ureteral obstruction (UUO) surgery on rat or stimulating human kidney-2 (HK-2) cell with transforming growth factor β1 (TGFβ1). After modeling, the rats in the SQP low dose group (SQP-L), SQP middle dose group (SQP-M) and SQP high dose group (SQP-H) were treated with SQP at 1.5, 3 or 6 g/kg/d, and the cells in the TGFβ1+SQP-L/M/H were treated with 2.5%, 5%, 10% SQP-containing serum. In in vivo assays, serum creatinine (SCr) and blood urea nitrogen (BUN) content were measured, kidney histopathology was evaluated., and α-smooth muscle actin (α‐SMA) expression was detected by immunohistochemistry. Interleukin-1β (IL-1β), interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) content, inhibitor of kappa B alpha (IKBα) and P65 phosphorylation were assessed. Meanwhile, cell viability, inflammatory cytokines content, α‐SMA expression, IKBα and P65 phosphorylation were detected in vitro experiment. Results. SQP exhibited reno-protective effect by decreasing SCr and BUN content, improving renal interstitial damage, blunting fibronectin (FN) and α‐SMA expression in RIF rats. Similarly, after the treatment with SQP-containing serum, viability and α‐SMA expression were remarkably decreased in TGFβ1-stimulated HK-2 cell. Furthermore, SQP markedly down-regulated IL-1β, IL-6, and TNF-α content, IKBα and RelA (P65) phosphorylation both in vivoand in vitro. Conclusion. SQP has a reno-protective effect against RIF in vivoand in vitro, and the effect is partly linked to nuclear factor-kappa B (NF-κB) pathway related inflammatory response, which indicates that SQP may be a candidate drug for RIF.DOI: 10.52547/ijkd.7546